New Type of Gear- cam Modular Reel - Lu Tiwen; Li Bo; Zhou Chaochao; Chen Dingfang (Jixie chuandong)
To improve the efficiency of harvester reel and improve the shortcomings of existing eccentric reel,a new device of gear- cam modular reel is presented. By a combination of gear and cam,through changing the reel speed in the rotation process and tine head vertically into the ear to improve reel efficiency. The main features of the device,the key parts of the design,including the cam profile design,mechanical analysis of the spindle and so on are described. By using MATLAB and Solid Works,a cam profile is designed,and by using ANSYS,the spindle statics analysis of the structure and vibration mode and natural frequency under dynamic load are got. By the design and analysis,the presented new reel is practicable.